The Bβ-sheet in the PAI-1 Molecule Plays an Important Role for Its Stability - Sui, Guang-Chao; Wiman, Björn (Thrombosis and Haemostasis, 2000)
We have investigated the B β-sheet in PAI-1 regarding its role for the stability of the molecule. The residues from His219 to Tyr241 (except for Gly230 and Pro240), covering the s2B and s3B strands, and in addition His185 and His190 were substituted by amino acids with opposite properties. The 23 generated single-site changed mutants and also wild type PAI-1 (wtPAI-1) were expressed in E. coli. Subsequently they were purified by heparin-Sepharose and anhydrotrypsin agarose affinity chromatographies. The stability of the purified PAI-1 variants was analyzed at 37° C and at different pHs (5.5, 6.5 or 7.5). At pH 7.5 and 37° C, single substitutions of the residues in the central portions of both strands 2 and 3 in the B β-sheet (Ile223 to Leu226 on s2B and Met235 to Ile237 on s3B), caused a significant decrease in stability, yielding half-lives of about 10–25% as compared to wtPAI-1. On the other hand, mutations at both sides of the central portion of the B β-sheet (Tyr221, Asp222, Tyr228 and Thr232) frequently resulted in an increased PAI-1 stability (up to 7-fold). While wtPAI-1 exhibited prolonged half-lives at pH 6.5 and 5.5, the PAI-1 variant Y228S was more stable at neutral pH (half-life of 9.6 h at pH 7.5) as compared to its half-life at pH 5.5 (1.1 h). One of the 4 modified histidine residues (His229) resulted in a variant with a clearly affected stability as a function of pH, suggesting that it may, at least in part, be of importance for the pH dependence of the PAI-1 stability. Thus, our data demonstrate that the B β-sheet is of great importance for the stability of the molecule. Modifications in this part causes decreased or increased stability in a certain pattern, suggesting effects on the insertion rate of the reactive center loop into the A β-sheet of the molecule.
Keywords: PAI-1; site-directed mutagenesis; serine proteinase inhibitor